RETRACTED ARTICLE: Tetramethylpyrazine relieves LPS-induced pancreatic β-cell Min6 injury via regulation of miR-101/MKP-1 - Dong Chen; Dong Cao; Ping Sui (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Dong Chen, Dong Cao & Ping Sui (2019) Tetramethylpyrazine relieves LPS-induced pancreatic β-cell Min6 injury via regulation of miR-101/MKP-1. Artificial Cells, Nanomedicine, and Biotechnology, 47(1), 2545–2552, DOI: 10.1080/21691401.2019.1628039Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors have been unable to verify their original data, and therefore have agreed to retract the article.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.